2017
DOI: 10.1038/srep41709
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory impedance is correlated with morphological changes in the lungs on three-dimensional CT in patients with COPD

Abstract: The forced oscillation technique provides information concerning respiratory impedance, which comprises resistance and reactance of the respiratory system. However, its relationship with morphological changes of the lungs in chronic obstructive pulmonary disease (COPD) remains unclear. Respiratory impedance and spirometric data were evaluated in 98 patients with COPD and 49 reference subjects. Wall thickness (WT) and airway intraluminal area (Ai) of third- to sixth-generation bronchi, and percentage low-attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 33 publications
(66 reference statements)
1
45
1
Order By: Relevance
“…The magnitude of the correlations between Ai and resistance differed according to the wave frequency, R5, and R20. This differed from previous studies in patients with COPD that showed no difference between R5 and R20 regarding a correlation with Ai . High‐frequency waves reflect back from large airways, and low‐frequency waves travel deep into the lungs .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The magnitude of the correlations between Ai and resistance differed according to the wave frequency, R5, and R20. This differed from previous studies in patients with COPD that showed no difference between R5 and R20 regarding a correlation with Ai . High‐frequency waves reflect back from large airways, and low‐frequency waves travel deep into the lungs .…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we validated the theoretical model that respiratory resistance reflects airway narrowing in asthmatic patients. Respiratory resistance (forward airway pressure) increased inversely based on bronchial airway calibre in chronic obstructive pulmonary disease (COPD) in our previous study, 28 which was also seen in asthmatic patients. Respiratory resistance may be useful to assess airway narrowing in pulmonary diseases with airflow obstruction.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As well as having a direct effect on an individual's ability to maintain fitness, ventilatory impairment as measured by FOT could also be a marker of morphological changes and extra-pulmonary manifestations in COPD that could affect exercise capacity, e.g. emphysema severity 30 or reduced muscle function. 31 Baseline X mean , DeltaXrs and FVC, which correlated with the change in 6MWD that occurred between finishing rehabilitation and 3 months later, are lung function measures of ventilatory impairment in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…31 Baseline X mean , DeltaXrs and FVC, which correlated with the change in 6MWD that occurred between finishing rehabilitation and 3 months later, are lung function measures of ventilatory impairment in COPD. Xrs (and Rrs) correlates strongly with percentage of emphysematous lung, 30 which is known to be poorly ventilated. Furthermore, Xrs correlates strongly with airway closure (as measured by FVC) in asthmatics during induced bronchoconstriction, 32 with closing volume in healthy subjects 33,34 and with the difference between plethysmographic TLC and single breath alveolar volume difference in COPD subjects.…”
Section: Discussionmentioning
confidence: 99%